MENGUAK REALITAS PRAKTIK SEDEKAH BUMI DI DESA CIASMARA KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Raden Atang Supriatna; Yogaprasta Adi Nugraha (CaLLs: Journal of Culture, Arts, Literature, and Linguistics)
Agriculture is one of the important sectors that contribute to Indonesian national income. However, agricultural development currently has a tendency to increase productivity it impacts on the agricultural system which tends to make agriculture as "commodities" and reduces the position of agriculture as an spiritual activity. Mainstreaming agriculture into "commodity" has an impact on the lost of cultural infrastructure that is supporting agriculture. This study aims to (1) see the existence of “Sedakah Bumi” practices in Ciasmara Village, Pamijahan District, Bogor Regency (2) Transformation practices of “Sedekah Bumi” in Ciasmara village, Pamijahan District, Bogor Regency. This study uses a Rapid-Ethnography approach or fast ethnography, located in the village of Ciasmara, Pamijahan District, Bogor Regency from March 2019 - August 2019. This research found that in Ciasmara village there is still the practice of “Sedekah Bumi”, but the form of the celebration is not in the form of a colossal celebration but the celebration in the form of private in the family. This form of transformation of the “Sedekah Bumi” emerged as a response from the respect of each component of society so as not to violate each other's main norms adopted by each group of people.